Step-by-step explanation:
We are asked to simply (2√5 + 3√2)². Using formula: (a + b)² = a² + b² + 2ab. Let's say 2√5 = a, 3√2 = b. So,
→ (a + b)² = a² + b² + 2ab
→ (2√5 + 3√2)² = (2√5)² + (3√2)² + 2(2√5)(3√2)
We are aware about the fact that root means 1/2 and square of root means 2/2 that is 1. Using this we get:
→ (2√5 + 3√2)² = 4(5) + 9(2) + 2(2√5)(3√2)
Solve the brackets, to do so first put the like terms in one box.
→ (2√5 + 3√2)² = 4(5) + 9(2) + 2(2*3)(√5)(√2)
Solve the rest calculations.
→ (2√5 + 3√2)² = 20 + 18 + 2(6)(√10)
→ (2√5 + 3√2)² = 38 + 12√10
Option (a) (38 + 12√10) is the correct option.
Answer:
A. Independent variable
Step-by-step explanation:
The prediction of a variable can be done if we have the independent variable. Which is the required variable that is used to determine the value of the other variable. The variable to be predicted is dependent on the required variable.
An independent variable can also be referred to as a predictor variable. When its value is known, it can be used to obtain the dependent variable.
The answer is 23 because they have to add up to 90 :) - beanz
x = 10
since GI bisects ∠DGH then ∠DGI = ∠IGH, hence
2x - 13 = x - 3 ( subtract x from both sides )
x - 13 = - 3 ( add 13 to both sides )
x = 10
Answer:
Cubic polynomial has zeros at x=−1x=−1 and 22, is tangent to x−x−axis at x=−1x=−1, and passes through the point (0,−6)(0,−6).
So cubic polynomial has double zero at x=−1x=−1, and single zero at x=2x=2
f(x)=a(x+1)2(x−2)f(x)=a(x+1)2(x−2)
f(0)=−6f(0)=−6
a(1)(−2)=−6a(1)(−2)=−6
a=3a=3
f(x)=3(x+1)2(x−2)f(x)=3(x+1)2(x−2)
f(x)=3x3−9x−6